'Dark triad' personality traits and risky sexual behaviour - Mauda, Lesley Takalani (My University, 2013)
This study investigated the relationship between the ‘dark triad’ personality traits and risky sexual behaviour (sociosexuality), and the effect of gender on the relationship. Participants consisted of two hundred and twenty-two (222) University of Limpopo students. Correlation analysis results indicate that, among males, primary psychopathy is positively associated with overall sociosexuality and secondary psychopathy is negatively associated with the behavioural component of sociosexualiy. Primary, secondary and overall psychopathy was positively related to risky sexual behaviour (sociosexuality). However, Machiavellianism, narcissism and overall psychopathy were not related to all dimensions of sociosexuality. Regression analysis results revealed that very few ‘dark triad’ personality traits have the capacity to predict risky sexual behaviour (sociosexuality). High risk socio-sexual behavioural features were predicted by the ‘dark triad’ personality traits mostly among females than among males. There were comparatively more factors associated with risky sexual behaviour among females than males in this sample. Generally, the ‘dark triad’ personality traits varied in relating with features of risky sexual behaviour. The nature of the relationship of ‘dark triad’ personality traits depends on the particular type of risky sexual behaviour. This is contrary to previous empirical findings that suggest that, when measured in a normal sample, correlates of the ‘dark triad’ personality traits will be the same. Recommendations were made on the basis of the results. Key words: ‘dark triad’, narcissism, psychopathy, Machiavellianism, sociosexuality.
Thesis (M.A. ( Clinical Psychology)) -- University of Limpopo, 2013
Keywords: ‘dark triad’; Narcissism; Psychopathy; Machiavellianism; Sociosexuality; Personality; Sex (Psychology)